Carga familiar en familias antioqueñas del Grupo Psicoeducativo del Departamento de Psiquiatría de la Universidad de Antioquia que tienen un miembro diagnosticado con trastorno afectivo bipolar (2011)
ABSTRACT: Objective: To determine family burden in a group of families from the psychoeducation group of the Department of Psychiatry of the Universidad de Antioquia who have a family member diagnosed with bipolar disorder. Method: Family burden was measured in 50 caregivers of people diagnosed with Bipolar Disorder using the “Escala de Carga Familiar (ECF)”, which is a Spanish adaptation of the Psychosocial Functioning Scale. Statistic processing and analysis was done with SPSS Version 17 using descriptive statistics, tendency analysis, means, and percentages. Results: 34 (68%) of the caregivers were women and 16 (32%) were men. Objective burden median of caregivers was 0.5 with interquartile range between 0.28 and 0.85 which shows a low objective burden. Attribution median was 0.50 with interquartile range between 0 and 1 showing a very low attribution. Finally, subjective burden median was 0.53 with interquartile range between 0.36 and 0.83 which shows a low subjective burden. Conclusions: Family burden in caregivers who take part in the psychoeducation group of the Department of Psychiatry of the Universidad de Antioquia is low. This could be explained by the support offered by the group and patients’ euthymia.